Brain Renin–Angiotensin System: Does It Exist?. Issue 6 (June 2017) - van Thiel, Bibi S.; Góes Martini, Alexandre; te Riet, Luuk; Severs, David; Uijl, Estrellita; Garrelds, Ingrid M.; Leijten, Frank P.J.; van der Pluijm, Ingrid; Essers, Jeroen; Qadri, Fatimunnisa; Alenina, Natalia; Bader, Michael; et al.
Abstract : Because of the presence of the blood–brain barrier, brain renin–angiotensin system activity should depend on local (pro)renin synthesis. Indeed, an intracellular form of renin has been described in the brain, but whether it displays angiotensin (Ang) I–generating activity (AGA) is unknown. Here, we quantified brain (pro)renin, before and after buffer perfusion of the brain, in wild-type mice, renin knockout mice, deoxycorticosterone acetate salt–treated mice, and Ang II–infused mice. Brain regions were homogenized and incubated with excess angiotensinogen to detect AGA, before and after prorenin activation, using a renin inhibitor to correct for nonrenin-mediated AGA. Renin-dependent AGA was readily detectable in brain regions, the highest AGA being present in brain stem (>thalamus=cerebellum=striatum=midbrain>hippocampus=cortex). Brain AGA increased marginally after prorenin activation, suggesting that brain prorenin is low. Buffer perfusion reduced AGA in all brain areas by >60%. Plasma renin (per mL) was 40× to 800× higher than brain renin (per gram). Renin was undetectable in plasma and brain of renin knockout mice. Deoxycorticosterone acetate salt and Ang II suppressed plasma renin and brain renin in parallel, without upregulating brain prorenin. Finally, Ang I was undetectable in brains of spontaneously hypertensive rats, while their brain/plasma Ang II concentration ratio decreased by 80% after Ang II type 1 receptor blockade. In conclusion, brain renin levels (per gram) correspond with the amount of renin present in 1 to 20 μL of plasma. Brain renin disappears after buffer perfusion and varies in association with plasma renin. This indicates that brain renin represents trapped plasma renin. Brain Ang II represents Ang II taken up from blood rather than locally synthesized Ang II. Abstract : Supplemental Digital Content is available in the text.